Children's diurnal cortisol activity during the first year of school. Issue 1 (2nd January 2017) - Yang, Pei-Jung; Lamb, Michael E.; Kappler, Gregor; Ahnert, Lieselotte
ABSTRACT: The present study examined 4- to 5-year-old British children's diurnal cortisol activity during their first year of school. The children's cortisol was measured before enrollment (baseline), upon enrollment, and both 3 and 6 months after enrollment. On each day, cortisol was sampled four times, providing information about the diurnal amount of cortisol secreted (AUCG ). Mixed-effect models were constructed to examine the way children's cortisol fluctuated over the course of the school year. Physiological activity was greater 3 months after enrollment, suggesting that some children reacted more to the challenge of school later than they did initially. Implications and suggestions for transitional practices and future research are discussed.